HUMAN EVOLUTION OF PIERRE TEILHARD DE CHARDIN AND ITS CONTRIBUTION TO THE UNDERSTANDING OF HARMONIOUS FAMILIES IN INDONESIA - Sudarsih, Sri; Soeprapto, Sri; Siswanto, Joko (Universitas Islam Negeri Alauddin Makassar, 2016)
A harmonious community life will bring a positive logical consequence for national development. The harmony society is determined by the relationship between individuals of one with the other individual. A sense of belonging, mutual respect, and respect is an important factor for the creation of a harmonious community life. Such values that should be fundamental in any behavior in daily life began to be abandoned. Evolution according to Teilhard de Chardin at the fact is that the motion is continuously development from simple led to the perfection. Humans will continue to evolve toward perfection, i.e. Point Omega. The Omega point is God. God is the Alpha and Omega. Perfection will be achieved through personalized with love in the presence of inverting. Chastity value in theory of human evolution according to Chardin will base the vital value. Love is the energy that will be capable of carrying a human on personalized, therefore love must be present in every activity of individuals as members of a family in Indonesia so that it will reach the personalization that will bring a logical consequence in harmony and happiness.